Peningkatan Kreativitas Belajar IPS Melalui Penerapan Model Quantum Teaching Pada Siswa Kelas IV SDN 02 Ngepungsari Tahun Pelajaran 2014/2015 - Ibrahim, Ibrahim; , Dra. Risminawati, M.Pd (2016)
This study aims to improve the creativity of social studies through the application of quantum model of teaching in the fourth grade students of SDN 02 Ngepungsari the academic year 2014/2015. This type of research is a classroom action research with the research design consists of four stages: planning, implementation, observation and reflection. Subjects were teachers and students of SDN 02 Ngepungsari fourth grade totaling 20 students. Techniques of collecting data through interviews, observation and documentation. Data were analyzed using interactive analysis, results showed creativity On indicators of student learning aspect has a great curiosity in the Pre Cycle by 35%, in the first cycle was 57.5%, in the second cycle of 82.5%. Aspects provide ideas and proposals in the Pre Cycle by 30%, in the first cycle was 50%, in the second cycle of 80%. In indicator of student learning aspect creativity has their own opinion on Pre Cycle by 25%, in the first cycle was 50%, in the second cycle by 75%. Aspects can work alone in the Pre Cycle by 30%, in the first cycle was 55%, in the second cycle by 77.5%. The conclusion is through the application of learning models can improve creativity Quantum Teaching social studies in grade IV SDN 02 Ngepungsari the academic year 2014/2015.